THE CORRELATION BETWEEN GADGET USE AND STUDENT LEARNING ACHIEVEMENT AT SMAN 21 BEKASI CITY - Apriyanto Apriyanto; Iswadi Iswadi (Universitas Indraprasta PGRI, 2023)
The goal of the study is to examine the relationship between gadget use and learning achievement. Quantitative methods are used by researchers. The research population was 276 students. The sample consisted of 73 students taken through random sampling. The researchers use questionnaires. To analyze the data, the researchers use using simple correlation and t test with SPPS Program. The finding: (1) There is a significant correlation between the use of gadgets and academic achievement of class XI students at SMAN 21 Bekasi City. The implication is that students can use gadgets in the learning process in the classroom because using gadgets can develop students' learning independence in solving questions from the teacher. Students who use gadgets in learning will get various kinds of learning resources from the Internet so that students will be more creative and innovative in the learning process.